HUBUNGAN ANTARA KEAKTIFAN DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS VII SMP SE-KECAMATAN PANDAK TAHUN PELAJARAN 2015/2016 - Arif Endarwanto (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
In a descriptive, the aim of this study was to find out activeness, learning motivation and science result. In a correlative, this study to find out the correlation between activeness and learning motivation on science result study of the 7th-grade student secondary school of subdistrict Pandak in academic year 2015/2016. The study samples were taken by proportional random sampling technique. The data of activeness and learning motivation were collected by using question and data of natural science achievement acquired by using multiple choice test. Data analyzed by using correlation test. The result of this research showed that the trend of activeness was in the very high category, learning motivation was in the medium category, meanwhile, achievement in natural science was in the high category. In a correlative, there is a correlation that positive and very significant between activeness and learning motivation on science result study of 7th-grade student secondary school of subdistrict Pandak in academic year 2015/2016.